Analisis dan Perancangan Sistem Informasi Laundry FreshCycle Berbasis Website Menggunakan Metode Waterfall - Illa Dwi Pratiwi; Ananda Argianto; Dias Dwi Utami; Tarisa Emaliana (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of information technology in the digital age has driven changes in various business sectors, including the laundry service industry. However, a number of laundry businesses still rely on manual record-keeping, which is prone to errors, data loss, and makes it difficult to monitor business performance. This study aims to design a web-based FreshCycle Laundry Information System as a digital solution to improve the speed, efficiency, and accuracy of laundry operations. The system was built using the Waterfall method, which includes the steps of analysis, design, implementation, testing, and maintenance. Analysis was conducted to identify the functional and non-functional requirements of the two main actors: the laundry administrator/owner and the cashier. System design involved the creation of context diagrams and Data Flow Diagrams (DFDs) to illustrate data flow and business processes. The implementation utilized the Laravel framework and MySQL database with features such as routing, the Blade templating engine, and Eloquent ORM. Testing was conducted using Blackbox Testing, which evaluates system functionality based on inputs and outputs without examining internal code. The results showed that all core functions, such as customer data management, services, transactions, reports, and user authentication, operate in accordance with specifications. The system has proven successful in improving operational efficiency, reducing recording errors, and simplifying the monitoring of laundry activities.